(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2015)
Film cooling process is one of the most important external cooling methods used for gas turbine blades. In the present study the effectiveness of multi –row film cooling process on flat plate was estimated. Three rows of film cooling were considered with three configurations which are: simple injection angle with uniform cooling holes distribution, compound injection angle with uniform cooling holes distribution and staggered distribution for film cooling holes with simple injection angle. The simulation of the three cases were performed for different Reynolds number under real operating conditions. Gambit –Fluent package was used for the numerical simulation. Three dimensional incompressible turbulent flow with k –Ɛ model for turbulence was used for the simulation. The results show that, the staggered distribution for the film cooling holes gives the best for effectiveness the cooled surface.